Constructing territorial development with local actors: dairy producers and their relationship with university knowledge. Issue 3 (3rd April 2022) - Llanez Anaya, Helmer Fernando
ABSTRACT: This article presents a case study on how dairy producers and a university are connected to generate territorial development in a municipality. The field of study along with in-depth semi-structured interviews showed that university knowledge reaches dairy farmers through weak ties and imitating production processes. This relationship makes it possible to show that the knowledge produced in academia reaches producers, even though there is no deliberate plan to bring these two local development actors together. This case study allows us to better understand local actors and the manner in which they can generate development in an area.